2022
DOI: 10.1002/rnc.6095
|View full text |Cite
|
Sign up to set email alerts
|

Event‐based adaptive sliding mode control for Euler–Lagrange systems with parameter uncertainties and external disturbances

Abstract: This article studies the robust tracking control problem for a class of uncertain Euler-Lagrange systems. An adaptive sliding mode control strategy is proposed to address the robust stability of the closed-loop systems with external disturbances and parameter uncertainties. An adaptive parameter estimator is constructed in the sensor node to deal with the unknown bound of uncertainties, and an event-triggering detector is located between the sensor node and the controller node. The introduction of event-trigge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…The tradeoff of system performance, control inputs, and communication/actuation resource can be clearly formulated by the designed event-triggered control method in this paper. From the form of the event triggering condition (22) and system state convergence boundary (33), it can be concluded that the parameters affecting the system performance indicators are 𝜆, 𝜂, and 𝜖. The bigger 𝜆 and the smaller 𝜂 and 𝜖 can result in fewer triggering times, which leads to higher the communication resource saving rates and smaller state convergence boundaries.…”
Section: Zeno Behavior Avoidancementioning
confidence: 99%
See 3 more Smart Citations
“…The tradeoff of system performance, control inputs, and communication/actuation resource can be clearly formulated by the designed event-triggered control method in this paper. From the form of the event triggering condition (22) and system state convergence boundary (33), it can be concluded that the parameters affecting the system performance indicators are 𝜆, 𝜂, and 𝜖. The bigger 𝜆 and the smaller 𝜂 and 𝜖 can result in fewer triggering times, which leads to higher the communication resource saving rates and smaller state convergence boundaries.…”
Section: Zeno Behavior Avoidancementioning
confidence: 99%
“…In other words, the event‐triggered control approaches can balance the control system performance and the usage of actuation and communication resources. Recently, the designs of trajectory tracking control under event‐triggered framework have been explored by a quality of works for Euler–Lagrange systems 33‐38 . In References 33‐35, adaptive technique combined by neural network‐based sliding mode control techniques was developed to construct event‐triggered control strategies for dealing with trajectory tracking control problems of the uncertain Euler–Lagrange system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, wind disturbance has a significant impact on the movement of small UAVs in the real world, particularly when the modeling is inaccurate. To circumvent this issue, the mainstream techniques typically include neural networks estimators [ 35 , 36 , 37 ], nonlinear observers [ 38 , 39 ] and adaptive estimators [ 40 , 41 ], etc. On the basis of the aforementioned factors, we neutralize the effect of disturbances, uncertainties and time-varying communication delays and achieve precise control of time-varying formations.…”
Section: Introductionmentioning
confidence: 99%